Mangrove habitat partitioning by Ucides cordatus (Ucididae): Effects of the degree of tidal flooding and tree-species composition during its life cycle - Wunderlich, A. C. [UNESP]; Pinheiro, M. A A [UNESP] (Springer Nature, 2013)
Environmental factors strongly affect mangrove crabs, and some factors modulate population structure and habitat partitioning during the crabs' life cycle. However, the effect of these environmental factors on habitat selection by mangrove crabs is still unknown. We evaluated habitat selection by the mangrove crab Ucides cordatus in mangrove forests with different degrees of predominance of Rhizophora mangle, Laguncularia racemosa or Avicennia schaueriana, two tidal flooding levels (less- and more-flooded), and two biological periods (breeding and non-breeding seasons). Sampling was conducted in four mangrove forests with different influences of these biotic and abiotic parameters. We used the data for sex ratio to explain environmental partitioning by this species. Females predominated in R. mangle mangroves, independently of the biological period (breeding or non-breeding seasons), and males predominated only in the less-flooded L. racemosa mangroves. The flooding level affected the sex ratio of U. cordatus, with a predominance of males in less-flooded mangroves, independently of the biological period; and a gender balance in the more-flooded mangroves only during the breeding season. Outside the breeding season, the largest specimens were recorded in the R. mangle mangroves, but in the breeding season, the largest crabs were recorded in the L. racemosa mangroves with a higher level of flooding. These results suggest that tree-species composition and tidal flooding level can have a significant effect on the habitat partitioning of sexes and sizes of the mangrove crab U. cordatus both during and outside the breeding season. © 2012 Springer-Verlag and AWI.
Keywords: Flood; Habitat selection; Neotropical mangroves; Sex ratio; Tidal effects; Ucides cordatus; breeding season; community composition; crab; ecological impact; environmental factor; flooding; habitat selection; life cycle; mangrove; Neotropical Region; population structure; sex ratio; tidal cycle; Avicennia; Decapoda (Crustacea); Laguncularia racemosa; Rhizophora mangle; Rhizophoraceae; Scylla